A New View of the Federal Debt and Budget Deficits: Comment - Milbourne, Ross; Richards, Daniel J. (American Economic Review, 2016)
In a recent paper (1984), Robert Eisner and Paul Pieper, present new calculations of the real value of the federal debt. Eisner and Pieper correctly take account of fluctuations in the market value of nominal assets and liabilities, and also take account of changes in real values wrought by inflation. They define an adjusted real deficit as the change in the real net debt of the government (liabilities less assets). Defining L(A) as the nominal value of already outstanding government liabilities (assets), P as the price level and P as its rate of change, and D as the conventionally measured deficit, Eisner-Pieper define their adjusted real deficit (D*/P) as